2016
DOI: 10.1038/ncomms12481
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide binding by the widespread high-affinity cyclic di-GMP receptor MshEN domain

Abstract: C-di-GMP is a bacterial second messenger regulating various cellular functions. Many bacteria contain c-di-GMP-metabolizing enzymes but lack known c-di-GMP receptors. Recently, two MshE-type ATPases associated with bacterial type II secretion system and type IV pilus formation were shown to specifically bind c-di-GMP. Here we report crystal structure of the MshE N-terminal domain (MshEN1-145) from Vibrio cholerae in complex with c-di-GMP at a 1.37 Å resolution. This structure reveals a unique c-di-GMP-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 50 publications
6
130
0
2
Order By: Relevance
“…Residues key for c-di-GMP recognition have been identified for some of these targets and the recognition mechanisms appear to differ significantly from that of the ATPase FleQ 59 . For example, recent work demonstrated that MshE binds c-di-GMP at its N-terminal domain primarily through hydrophobic interactions with a 24-residue-long RLGxx( L/V/I)(L/V/I )xx G ( L/V/I)(L/V/I )xxxxLxxxLxxQ sequence 67 .…”
Section: C-di-gmp Control Of Bacterial Secretion Systems (Ss)mentioning
confidence: 99%
“…Residues key for c-di-GMP recognition have been identified for some of these targets and the recognition mechanisms appear to differ significantly from that of the ATPase FleQ 59 . For example, recent work demonstrated that MshE binds c-di-GMP at its N-terminal domain primarily through hydrophobic interactions with a 24-residue-long RLGxx( L/V/I)(L/V/I )xx G ( L/V/I)(L/V/I )xxxxLxxxLxxQ sequence 67 .…”
Section: C-di-gmp Control Of Bacterial Secretion Systems (Ss)mentioning
confidence: 99%
“…A recent study showed that polymerization of MshA subunits is promoted by c-di-GMP binding via the ATPase MshE [17,28]. MshE binds c-di-GMP in its N-terminal domain [18,29]. Furthermore, structure of the MshE N-terminal domain revealed that c-di-GMP binds to the unique binding motifs consisting of a tandem array of two highly conserved 24-residue sequence RLGxx(L/V/I)(L/V/I)xxG(L/V/I)(L/V/I)xxxxLxxxLxxQ [29].…”
Section: Introductionmentioning
confidence: 99%
“…MshE binds c-di-GMP in its N-terminal domain [18,29]. Furthermore, structure of the MshE N-terminal domain revealed that c-di-GMP binds to the unique binding motifs consisting of a tandem array of two highly conserved 24-residue sequence RLGxx(L/V/I)(L/V/I)xxG(L/V/I)(L/V/I)xxxxLxxxLxxQ [29]. Binding to c-di-GMP activates MshE to polymerize the MshA pili, which facilitates attachment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, production of alginate in mucoid Pseudomonas aeruginosa requires c-di-GMP binding to the PilZ domain in Alg44, which is part of the alginate synthase complex (9). In addition to PilZ domains, c-di-GMP can be recognized by other receptors including GGDEF domains with an I-site, enzymatically inactive EAL domains, GIL domain, the MshEN domain, and c-di-GMPspecific riboswitches (10)(11)(12)(13)(14)(15)(16)(17)(18). Moreover, several c-di-GMP receptors function as transcriptional regulators, belong to diverse protein families, and regulate various cellular functions.…”
mentioning
confidence: 99%